Minimum Wage Impact on the Polish Economy - Krajewska, Anna; Kapela, Magdalena (Olsztyn Economic Journal, 2018)
This paper focuses on the analysis of the impact of the minimum wage on the Polish economy. It consists of three parts. The first part contains a short overview of the economic literature on the minimum wage in Poland and the results of research on this subject. The conclusions of these studies are unclear, which indicated the need to further analyze statistical data and assess the effects of raising the minimum wage in Poland. In the second part, an attempt is made to examine the correlation between the level of minimum wage and the rate of its change in Poland in the years 1992–2016 and basic economic indicators such as: level and rate of average wage growth, GDP, labor productivity, price growth dynamics and unemployment rate. Spearman’s correlation coefficients were used for this analysis. The third part concerns the perceived and potential effects of raising the minimum wage in 2017 to PLN 2,000 and introducing a minimum hourly rate of PLN 13. The focus is mainly on analyzing and assessing the impact of these decisions on the labor market in Poland. The positive aspects are presented as well as the dangers of introducing a minimum hourly wage. The article concludes that both the statistical data covering the last 25 years and the labor market analysis in 2017 do not support the negative effects of the minimum wage for the Polish economy.